Penerapan Metode Pembelajaran Interaktif Berbasis Quizizz untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran TIK di MTs Nurul Huda Cimanggu - Nuraisyah, Nuraisyah; Setiawan, Dena Latif (Indo-MathEdu Intellectuals Journal, 2025)
The lack of active student participation and low learning motivation in Information and Communication Technology (ICT) learning at MTS Nurul Huda Cimanggu became the background for this study. The study aimed to apply an interactive learning method based on Quizizz to improve student motivation and learning outcomes. The research method used was quantitative with a Pretest-Posttest Control Group Design. The research population consisted of 310 students, with a sample of two classes, namely the experimental class and the control class, each consisting of 32 students. Data were collected through observation, documentation, and tests, then analyzed statistically. The results of the study indicate that the use of Quizizz significantly improves student learning outcomes. The average post-test score for the experimental class was 76.56, while the control class scored only 59.38, with the hypothesis test showing a significant difference (p < 0.01). These findings confirm that the use of technology-based interactive media can create more engaging and effective learning. This study is expected to be a practical contribution for teachers in developing ICT learning strategies and to serve as a reference for further research on the use of technology in education